Lyme borreliosis: diagnostics, treatment and the role of healthcare services - Kortela, Elisa (fi=Turun yliopisto|en=University of Turku|, 2021)
Lyme borreliosis (LB) is the most common tick-borne disease in Europe, caused by spirochete Borrelia burgdorferi sensu lato. Approximately 3–16% of patients with B. burgdorferi infection develop neurological symptoms, leading to a disease called Lyme neuroborreliosis (LNB). Serological response in LB may take several weeks, which complicates the diagnostics in early LNB. The chemokine CXCL13 is a promising biomarker, the concentration of which starts to rise in acute LNB before intrathecal production of B. burgdorferi–specific antibodies begins. In Finland, LNB has been treated with a 3-week course of intravenous ceftriaxone. The aims of this study were to specify the manifestations of LNB in Finland, investigate the role of CXCL13 as a tool in the LNB diagnostics, compare oral doxycycline to intravenous ceftriaxone in the treatment of LNB, study the diagnostic accuracy of suspected LB with the most typical differential diagnoses, and evaluate the use of antibiotics and healthcare services in patients with suspected LB. The most typical signs and symptoms of LNB were painful meningoradiculitis, facial nerve palsy, Garin-Bujadoux-Bannwarth syndrome, headache and unspecific neck-shoulder pain. Cerebrospinal fluid CXCL13 concentration was elevated in the acute phase of infection and decreased rapidly after treatment. LNB patients who received doxycycline improved equally well as patients with ceftriaxone treatment. LB was unlikely in half of the patients with suspected LB. The most typical conditions causing the symptoms in patients with unlikely LB were of musculoskeletal, neurological, psychological and functional origin. Patients with unlikely LB used more healthcare services than patients with definite, probable or possible LB. Antimicrobial utilization did not differ among the groups of differing LB certainty. In conclusion, our results support the clinical use of CXCL13 in the diagnostics of LNB, and oral doxycycline in the treatment of LNB. Additionally, because various conditions may be confused with LB, physicians must pay attention to differential diagnostics of LB to avoid unnecessary antibiotic treatments and treatment delays.

Lymen borrelioosi: diagnostiikka, hoito ja terveydenhuollon palvelujen käyttö Lymen borrelioosi (LB) on tavallisin puutiaisvälitteinen sairaus Euroopassa. Sen aiheuttaa spirokeetta Borrelia burgdorferi sensu lato. Noin 3–16 %:lle potilaista kehittyy neurologisia oireita, jolloin sairautta kutsutaan Lymen neuroborrelioosiksi (LNB). Serologisen vasteen kehittyminen voi kestää viikkoja, mikä vaikeuttaa alkuvaiheen LNB:n diagnostiikkaa. Kemokiini CXCL13 on lupaava merkkiaine, jonka pitoisuus alkaa nousta akuutissa LNB:ssä ennen aivokalvojen sisäisen vastaainemuodostuksen alkamista. Suomessa LNB on hoidettu kolmen viikon kestoisella suonensisäisellä keftriaksonihoidolla. Tämän tutkimuksen tavoitteina oli täsmentää LNB:n ilmenemismuotoja Suomessa, tutkia CXCL13 hyödyllisyyttä LNB diagnostiikassa, verrata suun kautta otettavaa doksisykliiniä keftriaksoniin LNB:n hoidossa, tutkia epäillyn LB:n todennäköisyyttä ja tyypillisimpiä erotusdiagnooseja, sekä arvioida antibioottien ja terveyspalvelujen käyttöä potilailla, joilla epäillään LB:a. LNB-potilaiden yleisimmät oireet ja löydökset olivat kivulias hermojuurten tulehdus, kasvohermohalvaus, Garin-Bujadoux-Bannwarthin oireyhtymä, päänsärky ja epäspesifinen niska-hartiaseudun kipu. Aivo-selkäydinnesteen CXCL13 pitoisuus oli kohonnut akuutissa infektiossa ja väheni nopeasti hoidon jälkeen. Doksisykliinillä hoidetut LNB-potilaat paranivat yhtä hyvin kuin keftriaksonihoidon saaneet potilaat. LB oli epätodennäköinen puolella potilaista, joilla sairautta epäiltiin. Näillä potilailla oireiden taustalla oli useimmiten tuki- ja liikuntaelimistön ongelmia tai neurologisia, psykiatrisia tai toiminnallisia sairauksia. Potilaat, joilla LB osoittautui epätodennäköiseksi, käyttivät terveydenhuollon palveluja enemmän kuin potilaat, joiden LB-diagnoosi oli varma, todennäköinen tai mahdollinen. Mikrobilääkkeiden kulutuksessa ei ollut eroa näiden ryhmien välillä.